CONTEXTUAL ANALYSIS ON PUBLIC SERVICE ADVERTISEMENTS FROM THE MINISTRY OF EDUCATION AND CULTURE: OVERSEAS WORKER - Goziyah - -; Maulana - Yusuf; Imtihan - Hanim (Universitas Muhammadiyah Tangerang, 2022)
This study aims to conduct a contextual analysis of Public Service Advertisements from the Ministry of Education and Culture: OVERSEAS WORKER. The approach in this research is qualitative with content analysis method. The source of the data in this study is the Public Service Advertisement from the Ministry of Education and Culture: OVERSEAS WORKER which is uploaded through the YouTube channel of the Ministry of Education and Culture of the Republic of Indonesia. From this research, four data were found that can be analyzed by contextual discourse analysis, which are divided into the principle of personal interpretation, the principle of locational interpretation, the principle of temporal or situational interpretation, and the principle of analogy.